Origin, phenotype and autoimmune potential of T cells in human immune system mice receiving neonatal human thymus tissue - Talaie, Tara; Wang, Hui; Kuo, Wan-I; Danzl, Nichole; Gulsen, Mert R.; Wolabaugh, Amber N.; Ding, Xiaolan; Sykes, Megan; Li, Hao Wei (Frontiers in Immunology, 2023)
Robust human immune system (HIS) mice are created using human fetal thymus tissue and hematopoietic stem cells (HSCs). A HIS mouse model using neonatal human thymus tissue and umbilical cord blood (CB) HSCs (NeoHu) was recently described. We improved the model by removing the native murine thymus, which can also generate human T cells, and demonstrated definitively the capacity of human T cells to develop in a grafted neonatal human thymus. Human T cells derived from the neonatal thymus tissue appeared in peripheral blood early post-transplantation and CB-derived T cells appeared later. Naïve T cells were demonstrated in peripheral blood but effector memory and T peripheral helper phenotypes predominated later, in association with development of autoimmunity in some animals. Treatment of thymus grafts with 2-deoxyglucose (2-DG) increased the proportion of stem cells derived from injected HSCs, delayed onset of autoimmune disease, reduced early T cell reconstitution, and reduced effector/ memory T cell conversion. Younger neonatal human thymus tissue was associated with improved T cell reconstitution. While the NeoHu model bypasses the need for fetal tissue, it has yet to demonstrate equivalent reconstitution to fetal tissue, though 2-DG can improve results by removing native thymocytes prior to transplantation.